Las plataformas continentales: una división geopolítica del Mundo desde las coordenadas del materialismo filosófico de Gustavo Bueno - Armesilla Conde, Santiago Javier (Nómadas. Critical Journal of Social and Juridical Science, 2015)
We're trying to go deeper in the foregoing by Gustavo Bueno in the colophon of The Myth of the left about the possibility of the birth and development of a seventh generation left politically defined in a supranational homogeneous and not improvised continental platform.
Keywords: Continental platform; classess and States dialectics; geopolitics; philosophical materialism; left-wing ideologies; imperialism.